Influence of carbohydrates on the stability and structure of a hyperglycosylated human interferon alpha mutein - Ceaglio, Natalia Analia (2010)
Protein physical and chemical instability is one of the major challenges in the development of biopharmaceuticals during every step of the process, ranging from production to final delivery. This is particularly applicable to human recombinant interferon alpha-2b (rhIFN-α2b), a pleiotropic cytokine currently used worldwide for the treatment of various cancer and chronic viral diseases, which presents a poor stability in solution. In previous studies, we have demonstrated that the introduction of four N-glycosylation sites in order to construct a heavily glycosylated IFN variant (4N-IFN) resulted in a markedly prolonged plasma half-life which was reflected in an enhanced therapeutic activity in mice in comparison with the commercial non-glycosylated rhIFN-α2b (NG-IFN). Herein, we evaluated the influence of glycosylation on the in vitro stability of 4N-IFN towards different environmental conditions. Interestingly, the hyperglycosylated cytokine showed enhanced stability against thermal stress, acid pH and repetitive freeze-thawing cycles in comparison with NG-IFN. Besides, microcalorimetric analysis indicated a much higher melting temperature of 4N-IFN, also demonstrating a higher solubility of this variant as denoted by the absence of precipitation at the end of the experiment, in contrast with the NG-IFN behaviour. Furthermore, far-UV circular dichroism (CD) spectrum of 4N-IFN was virtually superimposed with that of NG-IFN, indicating that the IFN structure was not altered by the addition of carbohydrate moieties. The same conclusion could be inferred from limited proteolysis studies. Our results suggest that glycoengineering could be a useful strategy for protecting rhIFN-α2b from inactivation by various external factors and for overcoming aggregation problems during the production process and storage.